The absence of one’s intimate partner promotes dyadic competition through enhanced interbrain synchronization between opponents - Jia, Shuyu; Meng, Yujia; Gao, Yuan; Ao, Lihong; Yang, Lei; Wang, He; Liu, Yingjie (Frontiers in Psychology, 2024)
Grounded in Darwin's theory of sexual selection, this study utilized EEG hyperscanning technology to investigate the influence of the presence of romantic partners and the gender of competitors on the interbrain synchronization of female individuals during competitive contexts.The research results showed that in competitive interactions, there was a significant increase in Theta and Alpha frequency band activity between females and their competitors. interbrain synchronization was strongest when their partners were not nearby and females competed with same gender competitors. The research results indicate that intimate companionship has an impact on the early alertness and late cognitive execution mechanisms of female individuals in competition, and due to intimate relationships, females pay more attention to same-gender competitors. This study demonstrates that the presence of intimate partners can affect a female's competitive state and brain synchronization with opponents of different genders, improving the theoretical explanation of intimate relationships and competitive interactions.